Time perspective, future anxiety, and hope for success in individuals awaiting bariatric surgery - Kinga Tucholska; Bożena Gulla; Anna Grabowska; Piotr Major (Health Psychology Report, 2021)
Background The paper focuses on the problems of temporal functioning of obese individuals and of individuals prepared for bariatric treatment. The experience of time heavily weighs on many areas of human functioning, everyday activity, planning and achieving goals, engaging in pro-health behaviours, and in consequence on the quality of life and on physical health. Contingent on numerous factors, obesity may be related to focusing on particular aspects of time perspective. The aim of the study was to determine the specificity of particular temporal dispo-sitions in individuals prepared for bariatric surgery, and thus to devise suitable post-op psychological interven-tions.